Pengaturan dan Akibat Hukum Perkawinan Siri Online Ditinjau dari Perspektif Hukum Islam di Indonesia - Azizul Anwar; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2022)
The phenomenon in 2019 where the arrival of a virus called Covid-19 which required the public to limit all activities, including weddings. From this incident, one factor in the emergence of online serial marriages, because online serial marriages cost a minimum of money as well as the requirements for marriages that present few marriage witnesses. From this incident, one factor in the emergence of online serial marriages, because online serial marriages cost a minimum of money as well as the requirements for marriages that present few marriage witnesses. This study aims to reveal the Legal Arrangements and Consequences of Online Siri Marriage from the Perspective of Islamic Law in Indonesia. This research is a type of normative legal research or literary legal research or conservative legal research using a law approach and the legal system. This research was carried out by means of a library car study. The type of data used in this study is in the form of primary and secondary legal materials. The analysis of legal materials uses methods of description, codification (organization), understanding, and legal reasons/ideas. Achievements This research shows that currently there is no logical meaning related to unregistered marriage in the provisions of the law.